Lesbian Image and its Representation in Bodies Bodies Bodies (2022) Movie - Netasyabila Emanda Septa; Ali Mustofa (Jurnal Ragam Pengabdian, 2026)
This study will discuss how lesbian identity is represented and performed in the film Bodies Bodies Bodies (2022) in the form of characters Bee and Sophie. The textual analysis involves the analysis of the selected scenes where the researcher will examine how lesbian identity is produced in terms of visual signs, dialogue, emotional interaction and character behaviour. Based on the representation theories (Hall, 1997) and the concept of queer identity in cinema (Benshoff and Griffin, 2005), the analysis will be based on the production of meaning in the context of everyday interaction, bodily proximity, silence, vulnerability, and power dynamics. The results suggest that lesbian identity in the film is expressed as normalized and socially assimilated in an atmosphere of a modern youth, which is, at the same time, characterized by emotional insecurity, mistrust, and instability. Lesbian identity is enacted through emotional dependency, jealousy, reassurance, confrontation and power shifts and not through verbal declaration. The study adds to the discussion of the topic of queer representation in modern cinema by demonstrating how the performance of lesbian identity is produced and performed through minor visual and emotional practices in a mainstream film story.